A Rare Presentation of Choledochal Cyst in a Six-Month-Old Infant: Diagnostic and Surgical Challenges - Dita Novia Wulansari; Yusri Dianne Jurnalis; Jon Efendi (HM Publisher, 2025)
Background: Choledochal cysts (CCs) are rare congenital anomalies of the biliary tree, characterized by cystic dilation of the intrahepatic and/or extrahepatic bile ducts. While the classic triad of abdominal pain, jaundice, and a palpable abdominal mass is well-described, the presentation in infants can be subtle and often involves diagnostic and surgical challenges. This case report describes a rare presentation of a Todani Type 1 choledochal cyst in a six-month-old infant who presented primarily with abdominal distension, highlighting the diagnostic pathway and surgical management. Case presentation: A six-month-old female infant presented with a two-month history of progressive abdominal distension. There was a history of pale stools at two months of age that lasted for one week. Physical examination revealed a well-nourished infant with icteric skin and sclera and a distended abdomen with a palpable, mobile mass measuring 7x5 cm. Laboratory investigations revealed hyperbilirubinemia and elevated liver enzymes. Abdominal ultrasound and subsequent CT scan with contrast confirmed the presence of a Todani Type 1 choledochal cyst. The infant underwent successful surgical excision of the cyst and Roux-en-Y hepaticojejunostomy. The postoperative period was uneventful, and the patient was discharged in stable condition. Follow-up at one month showed good recovery and no signs of complications. Conclusion: This case highlights an atypical presentation of a Todani Type 1 choledochal cyst in a young infant, where the primary symptom was abdominal distension rather than the classic triad. Early diagnosis through imaging modalities like ultrasound and CT scan, followed by complete surgical excision and Roux-en-Y reconstruction, resulted in a favorable outcome. This case underscores the importance of considering choledochal cysts in the differential diagnosis of abdominal distension in infants, even in the absence of jaundice or pain.